STRENGTHENING CULTURE-BASED TOURISM BASED ON LOCAL WISDOM IN PURBAYAN TOURISM VILLAGE: IMPACT OF INDONESIA-THAILAND COLLABORATION 2024 - Setiawan, Ari; Hadi, Syamsul; Subekti, Nanang Bagus; Noongernchainphak, Ploypitcha; Arianti, Silvia; Muhammad Ilham, Maulana; Rosalina, Tita; Evita, Rossi; Yuni Dharta, Firdaus (SMARTINDO, 2025)
This community service program aims to strengthen culture-based tourism rooted in local wisdom in Purbayan Tourism Village through a collaborative partnership between Indonesia and Thailand. This service was held in the purbayan tourism village and the kings of Mataram who lived near Purbayan. This event was attended by 25 people from the management of Purbayan tourist village and representatives from Thailand. This community service activity lasted for 3 days, from May 20 to 23, 2024. Utilizing a Participatory Action Research (PAR) approach, the program was designed to empower local communities in identifying, developing, and promoting their unique cultural assets as sustainable tourism products. The activities included community capacity building workshops, development of experiential cultural tourism packages, international cultural exchange events, and digital marketing training. As a result, the community demonstrated increased awareness and participation in preserving and promoting their cultural heritage. Four thematic tourism packages were developed, integrating traditional arts, crafts, culinary experiences, and spiritual heritage. The collaboration with Thai tourism practitioners enriched local insights on sustainable tourism management and inspired innovations in storytelling and community-based governance. In addition, the program improved the digital competencies of local youth, leading to enhanced online visibility of the village.This initiative successfully illustrates how integrating local wisdom with international collaboration can foster inclusive, sustainable, and culturally rich tourism development. It also serves as a replicable model for other cultural villages seeking to build resilient tourism ecosystems grounded in community empowerment.